Perancangan Ulang Website MA Taruna Teknik Al Jabbar Berbasis User Centered Design (UCD) Berdasarkan Analisis Usability Menggunakan System Scale (SUS) - Panjaitan, Indah Riski; Zahra, Mauli Fathia; Angraini, Riska (CV. Information Technology Training Center - Indonesia (ITTC), 2026)
School websites serve as important media for delivering information and digital services to users. However, a website that does not pay attention to usability aspects can reduce its effectiveness. This study aims to redesign the website of MA Taruna Teknik Al Jabbar Medan based on the User Centered Design (UCD) approach, using usability analysis conducted with the System Usability Scale (SUS) method. The research employs a quantitative approach by distributing a SUS questionnaire consisting of 10 Likert-scale statements to students and teachers as website users. The SUS score results are used to identify usability issues in the existing website. Based on the analysis results, a website redesign is carried out following the UCD stages, including understanding the context of use, specifying user requirements, producing design solutions, and evaluating the design. The results of this study are expected to produce a website design that is more effective, efficient, and easy to use, as well as to improve user satisfaction with the school website.